The Relationship between Mobile Legends Playing Activity and Students’ Interest in Learning Physical Education - Zidhan, M.; Lukman, Lukman; Irmansyah, Johan; Qomara, Dwi (Sportify Journal, 2025)
This study was motivated by the increasing activity of playing Mobile Legends among students, which may reduce attention, discipline, and physical readiness in Physical Education, Sports, and Health learning. The purpose of this study was to examine the relationship between Mobile Legends gameplay and PJOK learning interest among Grade VIII students at MTsN 3 Kota Bima. This study used a correlational quantitative approach involving 49 male Grade VIII students selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through validity testing, reliability testing, Shapiro-Wilk normality testing, Pearson Product Moment correlation, and coefficient of determination. The results showed that the instrument was valid and reliable, data were normally distributed, and there was a significant negative relationship between Mobile Legends gameplay and PJOK learning interest, with r = -0.557 and p < 0.001. Coefficient of determination was 31.02%. Higher gameplay activity was associated with lower PJOK learning interest.